Star Excursion Balance Test anterior asymmetry is associated with injury status in division I collegiate athletes - Stiffler, M. R.; Bell, D. R.; Sanfilippo, J. L.; Hetzel, S. J.; Pickett, M. A.; Heiderscheit, B. C. (Journal of Orthopaedic & Sports Physical Therapy, 2017)
Study Design: Retrospective cohort. Background: Star Excursion Balance Test (SEBT) performance differs by sport in healthy collegiate athletes and lower extremity injury rates also vary among sports, sex, and athletic exposure. The relationship between SEBT performance and injury risk has not been evaluated with consideration of these additional variables which may be necessary to fully describe the relationship between SEBT performance and injury risk. Objectives: To assess the association between pre-season SEBT performance and non-contact injury occurrence to the knee or ankle in Division I collegiate athletes when controlling for sport, sex, and athletic exposure. Methods: SEBT performance, starting status, and injury status were reviewed retrospectively for NCAA Division I collegiate athletes from a single institution. A total of 147 athletes were healthy at the time of pre-season SEBT testing and either remained healthy (N=118) or sustained a non-contact injury to the knee or ankle (N=29) during their sport`s subsequent competitive season. Side-to-side asymmetries were calculated in each direction as the absolute difference in reach distance between limbs. SEBT reach distances and asymmetries were compared between groups using multivariable regression controlling for sport, sex, and athletic exposure (starter, non-starter). ROC curves were used to determine optimal sensitivity and specificity for significant models. Results: When controlling for sport, sex, and athletic exposure, the SEBT ANT direction side-to-side asymmetry, expressed as an absolute or normalized to limb length, discriminated between injured and non-injured athletes (AUCs >0.82). Conclusion: Assessing side-to-side reach asymmetry in the ANT direction of the SEBT may assist in identifying collegiate athletes who are at risk for sustaining non-contact injuries to the knee or ankle.